2014
DOI: 10.1371/journal.pone.0111079
|View full text |Cite|
|
Sign up to set email alerts
|

Wild-Type Mouse Models to Screen Antisense Oligonucleotides for Exon-Skipping Efficacy in Duchenne Muscular Dystrophy

Abstract: A readily available animal model is essential for rapidly identifying effective treatments for Duchenne muscular dystrophy (DMD), a devastating neuromuscular disorder caused by the lack of dystrophin protein, which results from frame-disrupting mutations in the DMD gene. Currently, the mdx mouse is the most commonly used model for antisense oligonucleotide (AO)-mediated exon skipping pre-clinical studies, with a mild phenotype. However, the accessibility of mdx mouse colonies particularly in developing countri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…Therefore, PMO is not expected to be delivered in terminally differentiated or nonregenerative cells such as cardiomyocytes. Furthermore, in in vivo studies, the systemic administration of PMO in healthy WT mice was not as effective as that in mdx mice under the same dosing regimens [41,42], whereas the systemic administration of renadirsen sodium produced clear exon-skipping activity even in WT mice in our study. Therefore, renadirsen is assumed to have cellular uptake superior to that of PMOs in muscle tissues and cells even under normal conditions.…”
Section: Discussioncontrasting
confidence: 66%
“…Therefore, PMO is not expected to be delivered in terminally differentiated or nonregenerative cells such as cardiomyocytes. Furthermore, in in vivo studies, the systemic administration of PMO in healthy WT mice was not as effective as that in mdx mice under the same dosing regimens [41,42], whereas the systemic administration of renadirsen sodium produced clear exon-skipping activity even in WT mice in our study. Therefore, renadirsen is assumed to have cellular uptake superior to that of PMOs in muscle tissues and cells even under normal conditions.…”
Section: Discussioncontrasting
confidence: 66%
“… 26 Notably, PNA AOs showed superiority to 2'Ome RNA and comparable activity to phosphorodiamidate morpholino oligomer (PMO) from local intramuscular studies. 27 However, the systemic potential of PNA in restoring dystrophin expression and rescuing the phenotypic pathology of mdx mice remains to be explored, particularly at doses comparable to those of 2'Ome RNA and PMO as reported. 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, we propose it may be possible to tread the path set for the first DMD exon skipping study reported by Kinali and colleagues 56 : an intramuscular injection into late-onset Pompe disease patients as a single-blind, placebo-controlled, dose-escalation, proof-of-concept study. Although our study was performed in MyoD induced primary fibroblast cells, uptake of PMO into muscle cells should not be a limitation since intramuscular injection of PMO in healthy mouse strains have shown efficient uptake by muscle cells 57 . From the many lessons learned, we hope that it does not take more than a decade to get a splice switching treatment for GSD II into the clinic.…”
Section: Discussionmentioning
confidence: 99%